2009
DOI: 10.1007/s12011-009-8476-9
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Protein-Based Optical Biosensor for Copper Ion Quantitation

Abstract: In the present study, spectroscopic determinations of copper ions using chimeric metal-binding green fluorescent protein (His6GFP) as an active indicator have been explored. Supplementation of copper ions to the GFP solution led to a remarkable decrease of fluorescent intensity corresponding to metal concentrations. For circumstances, rapid declining of fluorescence up to 60% was detected in the presence of 500 microM copper. This is in contrast to those observed in the case of zinc and calcium ions, in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 34 publications
3
31
0
Order By: Relevance
“…It is noteworthy to mention that our AsGFP is produced as a His-tag protein, so it can be suggested that the presence of additional histidine residues can enhance the quenching effect as shown for other GFPs. Many authors have confirmed a selective bond of copper with mutated GFP, in which some residues are changed to histidines [8,10,13], and have emphasized how the location and distance of the imidazole ring need to be very close to the GFP fluorophore in order to effectively quench the fluorescence [12].…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations
“…It is noteworthy to mention that our AsGFP is produced as a His-tag protein, so it can be suggested that the presence of additional histidine residues can enhance the quenching effect as shown for other GFPs. Many authors have confirmed a selective bond of copper with mutated GFP, in which some residues are changed to histidines [8,10,13], and have emphasized how the location and distance of the imidazole ring need to be very close to the GFP fluorophore in order to effectively quench the fluorescence [12].…”
Section: +mentioning
confidence: 99%
“…Fluorescence quenching has been observed by Hg 2+ [5] and Cu 2+ on an engineered chimeric GFP harbouring hexahistidine [8]. Moreover, the introduction of metalbinding sites onto the GFP surface places metals in close proximity to chromophore resulted in fluorescence quenching probably induced by energy transfer, at low concentrations (micromolar) of copper ions [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the genetically encoded fluorescent sensors based on green fluorescent protein can be applied to analyze the availability of copper in intracellular processes. Many of these applications require reporters with specific physicochemical properties which lead to continuous apparition of genetically modified fluorescent protein variants [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, metal-induced changes in fluorescence can be used to report the presence of specific metals in a solution or cell. The change in fluorescence induced by metals can occur either by static quenching [12], energy transfer between a colored metal ion and the chromophore [11], or by perturbations to the protein’s structure [10]. In some designs, cross-bridging metal sites have been added to a linker that connects two differently-colored FPs [13][15].…”
Section: Introductionmentioning
confidence: 99%